6. EVALUATION OF TREATMENT OUTCOMES FOR ORAL CANDIDIASIS IN HIV/AIDS PATIENTS AT THE CENTER FOR TROPICAL DISEASES, NGHE AN GENERAL FRIENDSHIP HOSPITAL (2022-2024) (Vietnam Journal of Community Medicine, 2025)
Objectives: The study aimed to evaluate the treatment outcomes for oral candidiasis in HIV/ AIDS patients at the Center for Tropical Diseases, Nghe An Friendship General Hospital.Methods: Non-randomized, non-controlled intervention study was employed.Results: 78.6% of the clinical lesions were gone after 4 weeks. Fungal testing showed negative results after 4 weeks as 78.6%. The negative HIV viral load before and after treatment for oral candidiasis increased from 11.9% to 35.7%, p < 0.05. The positive HIV viral load decreased significantly from 61.5% to 38.5%, p < 0.05. The failure rate after 4 weeks of treatment for oral candidiasis was 15.4%(6/39), of which the treatment failure in HIV/AIDS patients of the stages III and IV was 44.4% and 100.0%, respectively. The rate of adverse effects of fluconazole150mg was 11.4% (9/42). The most common adverse effects included nausea (16.7% (7/42), diarrhea (9.5%), abdominal pain (4.8%), and flatulence (4.8%), which were naturally gone after stopping treatment 1-3 days.Conclusions: The cure rate of oral candidiasis with fluconazole 150mg was 84.6%(33/39). The rate of adverse effects was 11.4% (9/42). The most common adverse effect was nausea 16.7% (7/42), which was gone 1-3 days after stopping treatment.
Keywords: HIV/AIDS; fungi; oral